Looking for trustworthy answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Get quick and reliable solutions to your questions from a community of seasoned experts on our user-friendly platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
To solve the quadratic equation [tex]\( 3x^2 + 22x + 7 = 0 \)[/tex], we can use the quadratic formula:
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
For the given equation, [tex]\(a = 3\)[/tex], [tex]\(b = 22\)[/tex], and [tex]\(c = 7\)[/tex]. Let's break down the solution step-by-step.
1. Calculate the Discriminant:
[tex]\[ \text{Discriminant} = b^2 - 4ac \][/tex]
[tex]\[ \text{Discriminant} = 22^2 - 4 \times 3 \times 7 \][/tex]
[tex]\[ \text{Discriminant} = 484 - 84 = 400 \][/tex]
2. Calculate the Roots:
Now, substitute the values into the quadratic formula:
[tex]\[ x = \frac{-b \pm \sqrt{\text{Discriminant}}}{2a} \][/tex]
[tex]\[ x = \frac{-22 \pm \sqrt{400}}{2 \times 3} \][/tex]
[tex]\[ x = \frac{-22 \pm 20}{6} \][/tex]
We have two cases to consider:
[tex]\[ x_1 = \frac{-22 + 20}{6} = \frac{-2}{6} = -\frac{1}{3} \][/tex]
[tex]\[ x_2 = \frac{-22 - 20}{6} = \frac{-42}{6} = -7 \][/tex]
So, the roots of the equation are:
[tex]\[ x = -\frac{1}{3}, -7 \][/tex]
3. Check the Roots:
We can verify the roots by substituting them back into the original equation:
For [tex]\( x = -\frac{1}{3} \)[/tex]:
[tex]\[ 3\left(-\frac{1}{3}\right)^2 + 22\left(-\frac{1}{3}\right) + 7 \][/tex]
[tex]\[ 3 \times \frac{1}{9} - \frac{22}{3} + 7 \][/tex]
[tex]\[ \frac{3}{9} - \frac{22}{3} + 7 = \frac{1}{3} - \frac{22}{3} + 7 \][/tex]
[tex]\[ = \frac{1 - 22 + 21}{3} = \frac{0}{3} = 0 \][/tex]
For [tex]\( x = -7 \)[/tex]:
[tex]\[ 3(-7)^2 + 22(-7) + 7 \][/tex]
[tex]\[ 3 \times 49 - 154 + 7 \][/tex]
[tex]\[ 147 - 154 + 7 = 0 \][/tex]
Both roots satisfy the original equation, confirming that the solutions are correct.
Thus, the solutions to the equation [tex]\( 3x^2 + 22x + 7 = 0 \)[/tex] are:
[tex]\[ \boxed{-\frac{1}{3}, -7} \][/tex]
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
For the given equation, [tex]\(a = 3\)[/tex], [tex]\(b = 22\)[/tex], and [tex]\(c = 7\)[/tex]. Let's break down the solution step-by-step.
1. Calculate the Discriminant:
[tex]\[ \text{Discriminant} = b^2 - 4ac \][/tex]
[tex]\[ \text{Discriminant} = 22^2 - 4 \times 3 \times 7 \][/tex]
[tex]\[ \text{Discriminant} = 484 - 84 = 400 \][/tex]
2. Calculate the Roots:
Now, substitute the values into the quadratic formula:
[tex]\[ x = \frac{-b \pm \sqrt{\text{Discriminant}}}{2a} \][/tex]
[tex]\[ x = \frac{-22 \pm \sqrt{400}}{2 \times 3} \][/tex]
[tex]\[ x = \frac{-22 \pm 20}{6} \][/tex]
We have two cases to consider:
[tex]\[ x_1 = \frac{-22 + 20}{6} = \frac{-2}{6} = -\frac{1}{3} \][/tex]
[tex]\[ x_2 = \frac{-22 - 20}{6} = \frac{-42}{6} = -7 \][/tex]
So, the roots of the equation are:
[tex]\[ x = -\frac{1}{3}, -7 \][/tex]
3. Check the Roots:
We can verify the roots by substituting them back into the original equation:
For [tex]\( x = -\frac{1}{3} \)[/tex]:
[tex]\[ 3\left(-\frac{1}{3}\right)^2 + 22\left(-\frac{1}{3}\right) + 7 \][/tex]
[tex]\[ 3 \times \frac{1}{9} - \frac{22}{3} + 7 \][/tex]
[tex]\[ \frac{3}{9} - \frac{22}{3} + 7 = \frac{1}{3} - \frac{22}{3} + 7 \][/tex]
[tex]\[ = \frac{1 - 22 + 21}{3} = \frac{0}{3} = 0 \][/tex]
For [tex]\( x = -7 \)[/tex]:
[tex]\[ 3(-7)^2 + 22(-7) + 7 \][/tex]
[tex]\[ 3 \times 49 - 154 + 7 \][/tex]
[tex]\[ 147 - 154 + 7 = 0 \][/tex]
Both roots satisfy the original equation, confirming that the solutions are correct.
Thus, the solutions to the equation [tex]\( 3x^2 + 22x + 7 = 0 \)[/tex] are:
[tex]\[ \boxed{-\frac{1}{3}, -7} \][/tex]
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.